POPULATION PHARMACOKINETICS OF INTRAVENOUS ALBUTEROL IN CHILDREN WITH STATUS ASTHMATICUS. Issue 1 (14th December 2015) - Vet, Nienke J; de Winter, Brenda CM; de Wildt, Saskia N; der Nagel, Bart CH van; AJ Knibbe, Catherijne; Koninckx, Muriel; de Hoog, Matthijs; Koch, Birgit CP
Abstract : Objectives: To develop a population pharmacokinetic model of R-albuterol and S-albuterol for children suffering from status asthmaticus following continuous intravenous administration. Methods: At the pediatric ICU 19 children suffering from severe status asthmaticus were treated using continuous intravenous albuterol in doses based on clinical symptoms (range 0.1–10 µg/kg/min). During therapy 111 blood samples were collected and analysed for R- and S-albuterol using a validated LC/MS-MS method. A population pharmacokinetic analysis was conducted using non-linear mixed effects modelling (NONMEM 7.2). Data was logarithmically transformed. Model selection criteria were decrease in objective function, diagnostic plots and NPDE. The covariates (range) analysed were bodyweight (7.8–70 kg), age (0.8–15.3 years), creatinine concentration (17–70 µmol/L), alanine transaminase (5–29 IU/L), and urea (1.6–4.8 mmol/L). Results: A two-compartment model with separated clearance for R- (16.3 L/h) and S-albuterol (8.8 L/h) best described the data. Separated values for central volume of distribution (12.9 L), peripheral volume of distribution (45.2 L) and intercompartmental clearance (20.0 L/h) did not improve the model. Between-subject variability was described for clearance of R-albuterol (42%), clearance of S-albuterol (37%) and central volume of distribution (280%). Weight is a significant covariate using a power function. The exponent of the powerfunction was fixed at 0.75 for clearance and intercompartmental and at 1 for central and peripheral volume of distribution. Estimation of the exponent resulted in similar values and did not improve the model. No other covariates were identified. Conclusion: The population pharmacokinetics of R- and S-albuterol are described. This model can be used to evaluate the correlation between albuterol pharmacokinetics and effect in a population pharmacokinetic-pharmacodynamic analysis.